Behavior in strategic settings: Evidence from a million rock-paper-scissors games - Dimitris Batzilis; Sonia Jaffe; Steven D. Levitt; John A. List; Jeffrey Picel (Games, 2019)
We make use of data from a Facebook application where hundreds of thousands of people played a simultaneous move, zero-sum game-rock-paper-scissors-with varying information to analyze whether play in strategic settings is consistent with extant theories. We report three main insights. First, we observe that most people employ strategies consistent with Nash, at least some of the time. Second, however, players strategically use information on previous play of their opponents, a non-Nash equilibrium behavior; they are more likely to do so when the expected payoffs for such actions increase. Third, experience matters: players with more experience use information on their opponents more effectively than less experienced players, and are more likely to win as a result. We also explore the degree to which the deviations from Nash predictions are consistent with various non-equilibrium models. We analyze both a level-k framework and an adapted quantal response model. The naive version of each these strategies-where players maximize the probability of winning without considering the probability of losing-does better than the standard formulation. While one set of people use strategies that resemble quantal response, there is another group of people who employ strategies that are close to k1; for naive strategies the latter group is much larger.
Keywords: C72; D03; 330; play in strategic settings; large-scale data set; Nash equilibrium; non-equilibrium strategies